Homicide investigation field guide - DuPre, D'Michelle P. (Academic Press, 2013)
This practical field guide contains many of the checklists necessary to guide the first responder step-by-step through procedures, tactics, and forensic techniques used in sudden death and violent death investigations. Using these protocols, techniques and checklists will ensure that a proper and complete investigation is undertaken at the death scene. Covers basic investigation protocols as well as protocols for sexual assaultContains diagrams on how to search the scene, how to sketch the scene, and physical evidence guidelines as well as a forensic photography primerIncludes a detailed checklist of who, what, where, when, why and how.